Dietary Capsaicin Improves Glucose Homeostasis and Alters the Gut Microbiota in Obese Diabetic ob/ob Mice - Song, Jun-Xian; Ren, Hui; Gao, Yuan-Feng; Lee, Chong-You; Li, Su-Fang; Zhang, Feng; Li, Long; Chen, Hong (Frontiers in Physiology, 2017)
Background: The effects of capsaicin on obesity and glucose homeostasis are still controversial and the mechanisms underlying these effects remain largely unknown. This study aimed to investigate the potential relationship between the regulation of obesity and glucose homeostasis by dietary capsaicin and the alterations of gut microbiota in obese diabetic ob/ob mice. Methods: The ob/ob mice were subjected to a normal, low-capsaicin (0.01%), or high-capsaicin (0.02%) diet for 6 weeks, respectively. Obesity phenotypes, glucose homeostasis, the gut microbiota structure and composition, short-chain fatty acids, gastrointestinal hormones, and pro-inflammatory cytokines were measured. Results: Both the low- and high-capsaicin diets failed to prevent the increase in body weight, adiposity index, and Lee’s obesity index. However, dietary capsaicin at both the low and high doses significantly inhibited the increase of fasting blood glucose and insulin levels. These inhibitory effects were comparable between the two groups. Similarly, dietary capsaicin resulted in remarkable improvement in glucose and insulin tolerance. In addition, neither the low- nor high-capsaicin diet could alter the α-diversity and β-diversity of the gut microbiota. Taxonomy-based analysis showed that both the low- and high-capsaicin diets, acting in similar ways, significantly increased the Firmicutes/Bacteroidetes ratio at the phylum level as well as increased the Roseburia abundance and decreased the Bacteroides and Parabacteroides abundances at the genus level. Spearman’s correlation analysis revealed that the Roseburia abundance was negatively while the Bacteroides and Parabacteroides abundances were positively correlated to the fasting blood glucose level and area under the curve by the oral glucose tolerance test. Finally, the low- and high-capsaicin diets significantly increased the fecal butyrate and plasma total GLP-1 levels, but decreased plasma total ghrelin, TNF-α, IL-1β and IL-6 levels as compared with the normal diet. Conclusions: The beneficial effects of dietary capsaicin on glucose homeostasis are likely associated with the alterations of specific bacteria at the genus level. These alterations in bacteria induced by dietary capsaicin contribute to improved glucose homeostasis through increasing short-chain fatty acids, regulating gastrointestinal hormones and inhibiting pro-inflammatory cytokines. However, our results should be interpreted cautiously due to the lower caloric intake at the initial stage after capsaicin diet administration.